Dowspuda and its broken heritage - Chojnowski, Kamil (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2020)
The catalyst for this Thesis was a recognised issues with managing cultural landscape in today Poland and the recent selling of Dowspuda to a private owner. The aim of the paper is to examine how a multidisciplinary approach can give better understanding of a historical landscape and can contribute to creation of a resilient cultural landscapes in a Polish setting. The paper reviews political perturbations in Central Europe and makes connection to history of Dowspuda, as changes that occurred throughout the history led Dowspuda into deterioration. Beyond the examination of literature, graphical material has been used to complement the historical narrative about the site. The discussion raises the subject of heritage ownership, establishing a matching management plan for the landscape heritage of Dowspuda, as well as participation of people in order to secure Dowspuda’s heritage and identity. The conclusions resulting from this work have the potential to guide future actions into relevant cultural landscape management in Poland.